Nesting and Foraging Preferences of Four Sympatric Species of Cavity-Nesting Leafcutting Bees (Hymenoptera: Megachilidae) - Dai, Qianlei; Hu, Junjie; Liu, Xuan; Wan, Jia; Wei, Jiabao; Yang, Dongshuo; He, Chunling (Insects (Basel, Switzerland), 2025)
Megachilidae are crucial pollinators of cultivated and wild vegetation, playing a vital role in ecosystem pollination services, however, there is still a lack of information regarding the ecology and behavior of these species. This study aims to analyze the nesting ecology strategies of four sympatric species of leafcutting bees and their interactions with pollen source plants. Data were collected from April to October from 2019 to 2022 in the Jiyuan section of the Taihang Mountain National Nature Reserve (approximately 35°10′–35°25′ N, 111°55′–112°10′ E) using trap nest methods. Through the dissection of nesting tubes, their structural characteristics were revealed, and the pollen sources collected by the bees were identified. Our results showed that nesting activity of leafcutting bees lasted from May to October, with a preference for nesting tubes of 6 to 10 mm in diameter and 131 to 170 mm in length. We documented 48 plant species used as foraging sources, belonging to 17 orders, 24 families, and 33 genera, with the Fagaceae family (9 species) being predominant. The results indicate that the distinctive traits of these species—such as the asynchronous nesting periods, the types of nesting materials, the dimensions of cavities, and differential utilization of floral resources—likely play a critical role in niche differentiation among sympatric species, thereby ensuring the maintenance and persistence of Megachilidae populations in this region.